2017
DOI: 10.1002/jwmg.21215
|View full text |Cite
|
Sign up to set email alerts
|

Sandhill crane roost selection, human disturbance, and forage resources

Abstract: Sites used for roosting represent a key habitat requirement for many species of birds because availability and quality of roost sites can influence individual fitness. Birds select roost sites based on numerous factors, requirements, and motivations, and selection of roosts can be dynamic in time and space because of various ecological and environmental influences. For sandhill cranes (Antigone canadensis) at their main spring‐staging area along the Platte River in south‐central Nebraska, USA, past investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…associated with water-based land-cover classes may decrease the aversion of roads and other disturbance features on the landscape, whereas activities within other land-cover classes may increase alertness and aversion to roads. Pearse et al (2017b) demonstrated that Sandhill Crane (Antigone canadensis) is less sensitive to disturbance in higher quality roosting habitat that has lower bank vegetation and wider channels within the central Platte River. It is possible that North American Gruidae species perceive greater Fig.…”
Section: Discussionmentioning
confidence: 99%
“…associated with water-based land-cover classes may decrease the aversion of roads and other disturbance features on the landscape, whereas activities within other land-cover classes may increase alertness and aversion to roads. Pearse et al (2017b) demonstrated that Sandhill Crane (Antigone canadensis) is less sensitive to disturbance in higher quality roosting habitat that has lower bank vegetation and wider channels within the central Platte River. It is possible that North American Gruidae species perceive greater Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Faanes and Le Valley (1993) also showed that Sandhill Crane roosting densities were increasing in areas with relatively abundant remaining wet meadow habitat. Pearse et al (2017) demonstrated that the probability of Sandhill Cranes roosting in a portion of the river is related to the amount of cornfield nearby only when channels are relatively narrow; however, their study did not evaluate the impact of lowland grasslands on roosting distributions. Anteau et al (2011) found that the use of cornfields by cranes increased with the quantity of wet grassland habitat within 4.8 km.…”
mentioning
confidence: 97%
“…However, the impact of these efforts on the roosting distribution of Sandhill Cranes remains largely unexamined. Several studies investigated Sandhill Crane roosting habitat in the CPRV and generally found that Sandhill Cranes prefer channels wider than 150 m, bank vegetation <1.5 m tall, and shallow water depths (<20 cm); they also prefer a lack of human disturbance, including roads, bridges, and structures (Krapu et al 1984, Iverson et al 1987, Folk and Tacha 1990, Norling et al 1992a, Davis 2001, Pearse et al 2017. In addition to being an important predictor of Sandhill Crane roosting habitat use, channel width is indicative of broader riverine habitat features in the CPRV, including channel morphology, hydrology, and sinuosity, that can also impact Sandhill Crane habitat suitability (Schumm 1963, Williams 1978, Johnson 1994, Kinzel et al 2009, Horn et al 2012.…”
mentioning
confidence: 99%
See 2 more Smart Citations